Risk Management Model for the Stunting Reduction Acceleration Program - Nuzul Liliana; Novita Tresiana; Noverman Duadji (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The issue of stunting is one of the issues carried out in the national strategic goals in the 2020-2024 RPJMN. The Indonesian government is strongly committed to reducing stunting, this is reflected in the policy of Presidential Regulation Number 72 of 2021 concerning Acceleration of Stunting Reduction. At the implementation level, the issue of stunting reduction is intervened through the Stunting Reduction Acceleration Program (PPS) which has been implemented by involving 20 K / L and implemented gradually in districts / cities, starting with 100 districts / cities in 2022. In 2024, the Government targets the stunting prevalence rate to be 14%, with an accelerated reduction in stunting prevalence of 7.5% from 2023. This document describes the risk management that should be used as an instrument in the PPS Program to achieve the 2024 target. We integrate findings from various policy studies and best practices to guide efforts to implement effective risk management used in the PPS Program. This research uses the Systematic Literature Review (SLR) method. With the SLR method, researchers can determine the strategies used in overcoming the problems faced and identify different perspectives related to the Risk Management model in the PPS Program. The implementation of the PPS policy in various countries proves that the stunting management program does not escape the risks in the implementation process. This risk may become an obstacle in achieving the goal of reducing stunting. Therefore, several countries have implemented policies related to risk management. Risk management is integrative and specifically applied according to technical programs in stunting interventions. Best practices in several countries, both developed and developing countries, in dealing with the issue of stunting use two risk management approaches. This approach is divided into executive management and operational management approaches. Executive management uses formal risk management, namely ISO 3100, which has been proven effective, especially in the management of health programs such as stunting issues in both developing and developed countries. However, management does not limit operational management as a risk owner unit to perform risk identification tools uniformly but uses specific and different tools in each stunting handling program called vernacular risk management.